2018
DOI: 10.1111/jphp.12935
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer activity of tetrandrine by inducing pro-death apoptosis and autophagy in human gastric cancer cells

Abstract: These results demonstrated that the antitumour effects of tetrandrine by inducing autophagy and apoptosis involving Akt/mTOR pathway. Thus, tetrandrine may be a promising lead compound to be further developed in future for cancer therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 32 publications
1
26
0
Order By: Relevance
“…In recently years, several researchers have focused on the anticancer properties of tetrandrine on cancer cells or animal models. These pharmacological studies indicated that tetrandrine has value in the prevention and treatment of multiple cancers, including colon cancer, [ 55–58 ] bladder cancer, [ 59,60 ] oral cancer, [ 61,62 ] prostate cancer, [ 63,64 ] ovarian cancer, [ 65 ] gastric cancer, [ 66,67 ] breast cancer, [ 68–70 ] pancreatic cancer, [ 70,71 ] osteosarcoma, [ 72 ] cervical cancer, [ 73 ] lung cancer, [ 74–76 ] liver cancer [ 77–79 ] and colorectal cancer, [ 80 ] both in vitro and in vivo . In addition, it also has revealed that tetrandrine displays significant anticancer activities mainly through the regulation of such signalling pathways as the AMP‐activated protein kinase (AMPK)/mammalian target of rapamycin (mTOR), [ 60 ] the phosphoinositide‐3‐kinase (PI3K)/protein kinase B (AKT), [ 81 ] the Hippo/Yes‐ associated protein (YAP), [ 82 ] the PI3K/AKT/mTOR, [ 69 ] the p38 mitogen‐activated protein kinases (p38‐MAPKs), [ 55 ] the wingless (Wnt)/β‐catenin, [ 83 ] the Wnt/cadherin, [ 65 ] the extracellular signal‐regulated kinase (ERK) MAP kinase and ERK, [ 84 ] the poly (ADP ribose) polymerase (PARP), [ 41 ] the caspases/Becline I/LC3‐I/II [ 61 ] and the caspase cascade and mitochondrial pathways.…”
Section: Introductionmentioning
confidence: 99%
“…In recently years, several researchers have focused on the anticancer properties of tetrandrine on cancer cells or animal models. These pharmacological studies indicated that tetrandrine has value in the prevention and treatment of multiple cancers, including colon cancer, [ 55–58 ] bladder cancer, [ 59,60 ] oral cancer, [ 61,62 ] prostate cancer, [ 63,64 ] ovarian cancer, [ 65 ] gastric cancer, [ 66,67 ] breast cancer, [ 68–70 ] pancreatic cancer, [ 70,71 ] osteosarcoma, [ 72 ] cervical cancer, [ 73 ] lung cancer, [ 74–76 ] liver cancer [ 77–79 ] and colorectal cancer, [ 80 ] both in vitro and in vivo . In addition, it also has revealed that tetrandrine displays significant anticancer activities mainly through the regulation of such signalling pathways as the AMP‐activated protein kinase (AMPK)/mammalian target of rapamycin (mTOR), [ 60 ] the phosphoinositide‐3‐kinase (PI3K)/protein kinase B (AKT), [ 81 ] the Hippo/Yes‐ associated protein (YAP), [ 82 ] the PI3K/AKT/mTOR, [ 69 ] the p38 mitogen‐activated protein kinases (p38‐MAPKs), [ 55 ] the wingless (Wnt)/β‐catenin, [ 83 ] the Wnt/cadherin, [ 65 ] the extracellular signal‐regulated kinase (ERK) MAP kinase and ERK, [ 84 ] the poly (ADP ribose) polymerase (PARP), [ 41 ] the caspases/Becline I/LC3‐I/II [ 61 ] and the caspase cascade and mitochondrial pathways.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, fangchinoline (10) and tetrandrine (9) remain the most studied constituents of S. tetrandra. Tetrandrine has broad-spectrum antitumor effects (Bhagya and Chandrashekar 2018;Liu 2017;Liu et al 2016) in many types of cancer cells, including human liver cancer (Zhang et al 2018a;Yu and Ho 2013), osteosarcoma Lu et al 2017), oral cancer (Lien et al 2017;Huang et al 2013), colon carcinoma (Meng et al 2004;Li et al 2019), gastric cancer (Bai et al 2018;Qin et al 2013), brain glioblastoma multiforme GBM 8401 cancer (Jiang et al 2019) and lung carcinoma (Chow et al 2018;Cho et al 2009). It also exhibits antineoplastic activity against gallbladder carcinoma (Zhu et al 2014), thyroid carcinoma B-CPAP cells ), prostatic carcinoma PC3 cells (Lan et al 2018), esophageal cancer , breast cancer (Guo and Pei 2019), pancreatic cancer (Singh et al 2018), nasopharyngeal carcinoma (Lin et al 2016(Lin et al , 2017b, acute megakaryoblastic leukemia (Liu et al 2017c), cervical cancer (Zhang et al 2018b) and renal carcinoma (Chen et al 2014(Chen et al , 2017a cells.…”
Section: Anti-inflammatory Effectsmentioning
confidence: 99%
“…A number of mechanisms are involved in the manner in which the constituents of S. tetrandra act against various carcinoma cells, including induction of tumor cell apoptosis (Zhu et al 2014;Bai et al 2018;Liu et al 2017b;Chen et al 2014;Wang et al 2017b;Fan et al 2017), tumor cell autophagy (Zhang et al 2018b;Lien et al 2017;Huang et al 2013;Bai et al 2018;Guo and Pei 2019;Fan et al 2017;Gao et al 2017), tumor cell cycle blockade (Singh et al 2018;Chen et al 2014;Luo et al 2016;Gao et al 2017) and inhibition of tumor cell invasion and metastasis (Zhang et al 2018a;Li et al 2017b;Shi et al 2017). Reversal of multidrug resistance is an additional important mechanism of the anticancer effects of tetrandine (9) and fangchinoline (10).…”
Section: Anti-inflammatory Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Membranes were incubated with secondary antibodies (1 : 10 000) for 1 h and treated with the Luminata Forte Western HRP Substrate. [25] The bands were quantified by ImageJ software.…”
Section: Western Blot Assaymentioning
confidence: 99%